Effects of Strategic Intervention on Developing Reading and Reading Comprehension Skills of the Learners - Swain, Ajay Kumar; Sethi, Jayamala (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The National Achievement Survey (NAS) was carried out all over the country on 13th November 201 to assess the learning level of students in classes- III, V and VIII in Government and Government aided schools. Low performance is one of the reasons which are called psychological dropout. Students‘ low performance in language hinders them to comprehend the higher-class competency in Language. Hence, the investigator conducted the study entitled ―Effects of Strategic Intervention on Developing Reading and Reading Comprehension Skills of the Learners‖. This study was carried out with two specific objectives like to identify the status of the Cuttack district in respect of the State Report card and to evolve strategies to improve the level of learning achievement of class viii students in the first language Odia. A survey- cum- experimental method was adopted to conduct this study. 40 students were selected randomly to conduct this study. Data was collected using the tool like achievement tests through pre-test and post-test procedures. The intervention period was one month. The post-test result was better than Pre-test. It proved that remedial learning package had a positive effect on enhancing the achievement level